Parametric excitation of very low frequency (VLF) electromagnetic whistler waves and interaction with energetic electrons in radiation belt. (1st March 2018) - Sotnikov, V; Kim, T; Caplinger, J; Main, D; Mishin, E; Gershenzon, N; Genoni, T; Paraschiv, I; Rose, D
Abstract: The concept of a parametric antenna in ionospheric plasma is analyzed. Such antennas are capable of exciting electromagnetic radiation fields, specifically the creation of whistler waves generated at the very low frequency (VLF) range, which are also capable of propagating large distances away from the source region. The mechanism of whistler wave generation is considered a parametric interaction of quasi-electrostatic whistler waves (also known as low oblique resonance (LOR) oscillations) excited by a conventional loop antenna. The interaction of LOR waves with quasi-neutral density perturbations in the near field of an antenna gives rise to electromagnetic whistler waves on combination frequencies. It is shown in this work that the amplitude of these waves can considerably exceed the amplitude of whistler waves directly excited by a loop. Additionally, particle-in-cell simulations, which demonstrate the excitation and spatial structure of VLF waves excited by a loop antenna, are presented. Possible applications including the wave-particle interactions to mitigate performance anomalies of low Earth orbit satellites, active space experiments, communication via VLF waves, and modification experiments in the ionosphere will be discussed.